(untitled) (Al-Qamar, 2022)
The purpose of this research is to trace the existence of the concept of Karma in the lives of the South Asians and the role it played in shaping the history of this land. As, it seems difficult to separate this concept from the religious ideologies of the people who belonged to this area. The term Karma in Hindu, Buddhist and Jain philosophy means somebody’s current and future lives are determined by that person’s behavior in this and previous lives. In other words, Karma is the sum of a person’s actions in this and previous states of existence and is viewed as the deciding factor for their fate in the existing and future lives. This concept of Karma was prevalent over a wider geographical area, as we know that there is a common world myth about the ‘Immortal Soul’. Hence, it can also be easily linked to the concept of immortality, which is also part of the three monotheistic religions of the world and can be traced in the history of every land, nation and civilization. Moreover, when we trace the religious history of this land, this is the one and only element that is similar between all the indigenous religions (Hinduism, Buddhism or Jainism) of this land and which in a way also binds all the religions together, despite of many dissimilarities. This concept of Karma can also be traced back to the time of the Indus Valley Civilization with the help of their archaeological remains in the absence of decipherable script.